2021
DOI: 10.1002/eom2.12081
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale properties of lead halide perovskites by scanning tunneling microscopy

Abstract: Since the introduction of lead halide perovskites, tremendous progress has been made regarding their stability, reproducibility and durability. However, one of the issues that remains is related to the interfacial atomic structure arrangement and structure-property relationship under optical and electrical stimuli. In this critical review, we highlight the recent progress using scanning tunneling microscopy (STM) to understand the nanoscale properties and dynamic processes occurring in these halide perovskite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 82 publications
(221 reference statements)
0
4
0
Order By: Relevance
“…In this direction, scanning tunneling spectroscopy (STS) has been considered as an efficient tool in probing the band edges and mid-gap states as well. The ability to probe the density of states (DOS) with energy and spatial resolutions has made this technique unique in various quantum dots and complex core–shell systems. …”
Section: Introductionmentioning
confidence: 99%
“…In this direction, scanning tunneling spectroscopy (STS) has been considered as an efficient tool in probing the band edges and mid-gap states as well. The ability to probe the density of states (DOS) with energy and spatial resolutions has made this technique unique in various quantum dots and complex core–shell systems. …”
Section: Introductionmentioning
confidence: 99%
“…Dedicated mechanistic studies of the conversion process remain scarce, and the main reason for this is that it is very difficult to achieve high temporal resolution and atomic resolution simultaneously. The combination of STM with a laser provides a viable solution to in situ probing of various atomic‐scale dynamics in MHPM, such as optical absorption, photoelectric conversion, charge dynamics, electron‐phonon coupling, etc [13c,d, 18d,e, 50, 68] . With this advanced technique, it is possible to gain insights into the internal mechanism of photovoltaics, which is of great importance for the development of PSCs, as this will provide useful guidelines for the design of high‐efficiency MHPM‐based photovoltaic devices.…”
Section: Discussionmentioning
confidence: 99%
“…In this Perspective, we highlight the recent progress of SMA-STM to investigate light–matter interactions, starting with one of the very first investigated systems: CNTs and QDs. For the interested reader, additional review articles on optical STM can be found in refs . We further show how the development of the SMA-STM technique has been extended to expand the classes of materials that can be investigated by SMA-STM, including CDs, clusters, and thin films.…”
Section: Introductionmentioning
confidence: 95%